Karol May w slowie i w obrazie - May, Karl Friedrich, 1842-1912.; May, Karl Friedrich, 1842-1912. ([Zielona Gora : E. Jarmolkiewicz, 1994)
Polish translation of short stories about American Indians and the American West originally written in German. For ages 9-12.
Winnetou I -- Winnetou II -- Syn Lowcy Niedzwiedzi -- Skarb w Srebrnym Jeziorze -- Krol Nafty -- Old Shatterhand.
Keywords: Indians of North America -- Juvenile fiction; Western stories; Western stories